Confirmatory Factor Analysis of the Child Feeding Questionnaire: A Measure of Parental Attitudes, Beliefs and Practices About Child Feeding and Obesity Proneness - Valia Rachmawati; Ajeng Aliya Zahwa; Angeliq Kezia Haloho (CV. Akademi Merdeka, 2025)
This study aimed to examine the construct validity and reliability of the Child Feeding Questionnaire (CFQ) within the context of parental feeding practices and risk of childhood obesity in Indonesia. The instrument consists of three core constructs: Beliefs, Parental Attitudes, and Practices. A confirmatory factor analysis (CFA) was employed to assess convergent validity, discriminant validity, and internal consistency of the measurement model. The results indicated that the Beliefs and Parental Attitudes constructs demonstrated satisfactory internal consistency, as indicated by Cronbach’s Alpha and Composite Reliability values exceeding the recommended thresholds. However, the Practices construct demonstrated low reliability and weak indicator loadings, suggesting the need for revision or further development. Discriminant validity among the constructs was established based on the Fornell-Larcker criterion and HTMT values. Nevertheless, the overall model fit indices did not meet acceptable standards, primarily due to the weaknesses observed in the Practices construct. These findings the underscore importance of culturally adapting and refining the CFQ before its use in research or intervention programs aimed at promoting healthy feeding behaviors and preventing childhood obesity.